MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PEMBELAJARAN KIMIA - Rina Hardianti; Vanny MA Tiwow; Gamar (LPPM Universitas Cipta Mandiri, 2025)
This research aimed to increase student’s motivation and learning achievment in chemistry trough the implementation of the Culturally Responsive Teaching (CRT) approach combined with the Discovery Learning model. The research was counducted in grade XA of SMA Negeri 2 Palu withs in 36 students during the 2024/2025 academic year, using the Kemmis and McTaggart model that carried out in two cycles consisting of planning, action, observation, and reflection. The data were collected using learning achievement tests and observation, and analyzed both quantitatively and qualitatively. The results of the research test is showed student’s learning motivation, initialy categorized as well enough, improved to a good level by the end of the second cycle. Similarly, the average learning outcomes increased from 68.7 in the first cycle to 81.9 in the second cycle, with classical mastery improving from 64% to 86%. The using of CRT approaches as an integration of local cultural contexts, such as the use of ikan fufu grilling to explain Lavoisier’s Law and the preparation of kue tetu to illustrate Proust’s Law, enhance students comprehensive of chemisty concept and also increases the motivation and engangement in learning Chemistry. So that, the researcher indicates that the Culturally Responsive Teaching approaches as an effective strategy to create meaningful, contextual, and student-centered learning in chemistry learning.